Calibration of therapeutic ultrasound equipment - Guirro, Rinaldo; Serrão, Fábio; Elias, Daniela; Bucalon, Antonio José [UNESP] (Elsevier, 1997)
Temporal and spatial acoustic intensity (SATA) of therapeutic ultrasound (US) equipment should be monitored periodically. In order to evaluate the conditions of US equipment in use in the city of Piracicaba-Sao Paulo, Brazil, 31 machines - representing all Brazilian manufacturers - were analysed under continuous and pulsed conditions at a frequency of 1 MHz. Data about temporal and spatial acoustic intensity were collected and the use of equipment was surveyed. Intensities of 0.1, 0.2, 0.5, 0.8, 1.0, 1.5, 2.0, 2.5 and 3.0 Wcm -2, indicated on the equipment panel were analysed using a previously calibrated digital radiation pressure scale, model UPM-DT-1 (Ohmic Instruments Co). The acoustic intensity (I) results were expressed as superior and inferior quartile ranges for transducers with metal surfaces of 9 cm 2 and an effective radiation area (ERA) Of 4 cm 2. The results under continuous conditions were: I 0.1 = -20.0% and -96%. I 0.2 = -3.1% and -83.7%. I 0.5 = -35.0% and -86.5%. I 0.8 = -37.5% and -71.0%. I 2.5 = -49.0% and -69.5%. I 3.0 = -58.1% and -77.6%. For pulsed conditions, intensities were: I 0.1 = -40.0% and -86.2%. I 1.0 = -50.0% and -86.5%. I 1.5 = -62.5% and -82.5%. I 2.0 = -62.5% and -81.6%. I 2.5 = -64.7% and -88.8%. I 3.0 = -87.1% and -94.8%. In reply to the questionnaire drawn up to check the conditions of use of equipment, all users reported the use of hydrosoluble gel as a coupling medium and none had carried out previous calibrations. Most users used intensities in the range of 0.4. to 1.0 Wcm -2 and used machines for 300 to 400 minutes per week. The majority of machines had been bought during the previous seven years and weekly use ranged from less than 100 minutes to 700 minutes (11 hours 40 minutes). Findings confirm previous observations of discrepancy between the intensity indicated on the equipment panel and that emitted by the transducer and highlight the necessity for periodic evaluations of US equipment.
Keywords: Dosimetry; Output power; Radiation force balance; Therapeutic ultrasound; calibration; dosimetry; hydrogel; monitoring; priority journal; sound intensity; transducer; ultrasound; ultrasound therapy